Digital Citizenship and Political Engagement - Vromen, Ariadne. author. aut Link
XI, 278 p. 16 illus.
Keywords: This book considers the radical effects the emergence of social media and digital politics have had on the way that advocacy organisations mobilise and organise citizens into political participation. It argues that these changes are due not only to technological advancement but are also underpinned by hybrid media systems, new political narratives, and a new networked generation of political actors. The author empirically analyses the emergence and consolidation within advanced democracies of online campaigning organisations, such as MoveOn, 38 Degrees, Getup and AVAAZ. Vromen shows that they have become leading political advocates, and influential on both national and international level governance. The book critically engages with this digital disruption of traditional patterns of political mobilisation and organisation, and highlights the challenges in embracing new ideas such as entrepreneurialism and issue-driven politics. It will be of interest to advanced students and scholars in political participation and citizen politics, interest groups, civil society organisations, e-government and politics and social media.